доказать тождество: (cos2x+sin^2x)/sin2x=1/2 ctgx

(1+sinx+cosx)/(1+sinx-cosx)=ctg x/2

(cos3x+cos4x+cos5x)/(sin 3x+sin 4x+sin5x)=ctg 4x

(1+2cosx+cos2x)/(cos2x-cos3x+cos4x)=tg3x

упростить выражения: 1 + (сos4x / tg (3пи/4-2x))

tg (x - 5пи/4)*2 sin^2 (x + 5пи/4)

ctg (3x/2 + 5пи/4)*(1-sin (3x-пи))

1

Ответы и объяснения

2013-02-02T12:30:58+00:00

1. (cos2x+sin²x)/sin2x=0,5*ctgx;

(cos²x-sin²x+sin²x)/sin2x=cos²x/2*sinx*cosx=0,5*(cosx/sinx)=0,5*ctgx. - доказанно.

 

2. (1+sinx+cosx)/(1+sinx-cosx)=ctg(x/2);

(1+sin(π/2-x)+sinx)/(1+sinx-sin(π/2-x))=(1+2*sin(π/4)*cos(π/4-x))/(1+2*sin(x-π/4)*cos(π/4))=(1+√2*cos(π/4-x))/(1+√2*sin(π/4-x))=ctg(x/2). - доказанно.

 

3. (cos3x+cos4x+cos5x)/(sin3x+sin4x+sin5x)=((2*cos4x*cosx)+cos4x)/((2*sin4x*cosx)+sin4x)=cos4x(2cosx+1)/sin4x(2cosx+1)=cos4x/sin4x=ctg4x - доказанно.

 

4. (1+2cosx+cos2x)/(cos2x-cos3x+cos4x)=(2cos²x+2cosx)/(2*cos3x*cosx-cos3x)=2cosx(cosx+1)/cos3x(2cosx-1)= - дальше ума не приложу, как только не пробовал)) возможно, в условии ошибка у тебя?